I. Banerjee-Dube (2018). Una historia de India moderna (Vol. I: India colonial) (Trad. M. Capetillo). México: El Colegio de México. 356 pp. - Lorenzen, David N. (Estudios de Asia y África, 2019)
I. Banerjee-Dube (2018). Una historia de India moderna (Vol. I: India colonial) (Trad. M. Capetillo). México: El Colegio de México. 356 pp.